EFEK TAYANGAN SINETRON TELEVISI SWASTA TERHADAP SIKAP DAN PERILAKU ANAK - Abraham, Firda (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
The purposeof this researchis to describe the attitudes and behavior of the impressions soap opera, with asurvey method. The resultsshowed that "sinetrons "have a strong effecton attitudes and behavior. The Effectsare most likely overlapon there ligious "sinetrons ", reality of the past (history), as well as "sinetrons "that containa romantic story. Instead, the effectis not dominated by shows like horror and mysticism. Thechild inspired toimitate diction (words), hairstyle, clothing/fashion whic his a form of behavior thatis quite dominant that realizedby children.